2015
DOI: 10.1093/gerona/glr188
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in CT Scan Measures of Thigh Muscle 2 Months After Hip Fracture: The Baltimore Hip Studies

Abstract: The observed asymmetry is consistent with the effect of disuse and inflammation in the affected limb along with training effects in the unaffected limb due to the favoring of this leg with ambulation during the postfracture period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Adipose tissue (−100 to −50 in Hounsfield units) in the designated area was distinguished by a bimodal image histogram resulting from the distribution of CT numbers of adipose tissue and muscle [ 14 ]. The ATR was expressed bilaterally as the ratio of the area of intramuscular adipose tissue to the CSA [ 15 ]. The CSA was measured three times on both the non-operated and operated sides by three independent examiners in the TIP group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adipose tissue (−100 to −50 in Hounsfield units) in the designated area was distinguished by a bimodal image histogram resulting from the distribution of CT numbers of adipose tissue and muscle [ 14 ]. The ATR was expressed bilaterally as the ratio of the area of intramuscular adipose tissue to the CSA [ 15 ]. The CSA was measured three times on both the non-operated and operated sides by three independent examiners in the TIP group.…”
Section: Methodsmentioning
confidence: 99%
“…Even though CT imaging has been used to measure muscle size and quantify muscle pathology associated with hip fractures, few studies have compared the fractured and contralateral sides [15]. A number of studies using CT imaging of the gluteus muscle and the waist and thigh show the relationship between sarcopenia and life expectancy [13,[18][19][20][21].…”
Section: Surgical Technique Preparationmentioning
confidence: 99%
“…Muscle changes following emergency surgery for hip fractures has also been studied. Miller et al showed that following emergency surgery for hip fractures, there remained a significant reduction in thigh muscle CSA on the operated fractured leg, compared to the non-fractured leg, at 2 months [ 50 ]. Such changes may be prolonged to 3.5 years according to a different study [ 51 ].…”
Section: Diagnosing Sarcopeniamentioning
confidence: 99%